PENGARUH PENAMBAHAN TAWAS TERHADAP SIFAT MIKROBIOLOGI, FISIK DAN LAMA SIMPAN MIE - Nurrahman -; Joko Teguh Isworo (JURNAL LITBANG, 2007)
Boilling noodle by tawas solution was decrease sum of microbes and increaselong time of storeage. Higher concentration of tawas solution had effect decrease sum of microbes and increase long time of storeage. The research result was be analysis by ANOVA on 0.05 significant thas this was effect boiling by concentration of tawas solution on total of microbes and long time of storeage on noodle. Boilling noodle by tawas solution had trend increase noodle elasticity, although the effect was not significant.Key words : tawas, property of microbiologi, property of fisic and long time ofstoreage